Stepping Beyond Efficacy: Understanding the User Experience of Wearables for Children with Idiopathic Toe Walking in the Natural Setting - LouAnne Boyd; Rahul Soangra; Lara Mukhar; Rachel Kling; Marybeth Grant Beuttler (Human Factors in Healthcare, 2023)
Idiopathic Toe Walking is an atypical gait pattern that results in limited mobility, pain, and higher risk of falling. Current therapeutic interventions lack the ability to be implemented outside the clinic or lab. Beyond this, it is unclear if gait analysis and real-time feedback is technologically feasible to attain within a user's natural environment. In our research we aimed to understand the child and parent participants’ experience of an innovative wearable system. We surveyed children and parents after the deployment of a functional prototype with real time vibrotactile feedback for awareness of toe walking via a shoe insert paired with a smartphone for visual feedback. Findings revealed insights into design considerations for wearable technologies for children. Factors such as comfort of using the system (physically and psychologically), child's perception and response to the vibrotactile feedback, and children and parents’ perception of reduced fall risk, pain, and stigma are discussed.